Language Science and Intergenerational Learning in a Science Center. - Moore, Leslie C.; Babel, Anna; Patson, Nikole D.; Wagner, Laura; Campbell-Kibler, Kathryn; Clopper, Cynthia G.; Frush Holt, Rachael; Speer, Shari (Journal of Museum Education)
In this case study, we discuss how language science can promote intergenerational learning in informal learning institutions. We describe our work with and at the Center of Science and Industry (COSI) over the past decade, explain what language science is, and relate how we have leveraged it to engage visitor groups. We then focus on two projects, in which linguistic diversity was centered: (1) a study of science center programs that engage young emergent bilinguals and their families and (2) an outreach project to develop and implement language science activities about Spanish to be conducted in Spanish and/or English. Each part of our story provides different insights into intergenerational learning in the science center context, the key role played by language therein, and the transformative potential of language science in creating meaningful family experiences and promoting bi/multilingualism in informal learning spaces.